A Novel Peptide Derived from Human Apolipoprotein E Is an Inhibitor of Tumor Growth and Ocular Angiogenesis - Bhattacharjee, Partha S. (Public Library of Science, 2011)
Angiogenesis is a hallmark of tumor development and metastasis and now a validated target for cancer treatment. We previously reported that a novel dimer peptide (apoEdp) derived from the receptor binding region of human apolipoprotein E (apoE) inhibits virus-induced angiogenesis. However, its role in tumor anti-angiogenesis is unknown. This study demonstrates that apoEdp has anti-angiogenic property in vivo through reduction of tumor growth in a mouse model and ocular angiogenesis in a rabbit eye model. Our in vitro studies show that apoEdp inhibits human umbilical vein endothelial cell proliferation, migration, invasion and capillary tube formation. We document that apoEdp inhibits vascular endothelial growth factor-induced Flk-1 activation as well as downstream signaling pathways that involve c-Src, Akt, eNOS, FAK, and ERK1/2. These in vitro data suggest potential sites of the apoE dipeptide inhibition that could occur in vivo. This is the first evidence that a synthetic dimer peptide mimicking human apoE has anti-angiogenesis functions and could be an anti-tumor drug candidate.